Modeling variables associated with personal recovery among service users with mental disorders using community-based services. (March 2019) - Fleury, Marie-Josée; Sabetti, Judith; Bamvita, Jean-Marie; Grenier, Guy
Background: Mental health research is evolving toward the identification of conceptual models and associated variables, which may provide a better understanding of personal recovery, given its importance for individuals affected by mental disorders (MDs). Aims: This article evaluated personal recovery in a sample of adults with MDs using an adapted conceptual framework based on the Andersen behavioral model, which evaluates predisposing, enabling and needs factors in service use. Methods: The study design was cross-sectional and included 327 mental health service users recruited across four local health service networks in Quebec (Canada). Data were collected using seven standardized instruments and participant medical records. Structural equation modeling was performed. Results: Quality of life (QOL), an enabling factor, was most strongly associated with personal recovery. Health behavior variables associated with recovery included the following: use of alcohol services, having a family physician, consulting a psychologist, use of food banks, consulting fewer professionals and not using drug services. Regarding needs factors, higher numbers of needs, lower severity of unmet health, social and basic needs and absence of mood disorders were also associated with personal recovery. No predisposing factors emerged as significant in the model. Conclusion: Findings suggest that QOL, needs variables and comprehensive service delivery are important in personal recovery. Services should be individualized to the health, social and basic needs of service users, particularly those with mood disorders or co-occurring mental health/substance use disorders.